(3QSGdI Tchi Ydi dSGf GdeOQSI GdbOQGhjI HOeTbs - (3eMeO Hf Rjf GdOjf gdGd GdMfaj,J (B1012 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi CPgH YfG GdMRf hHYO aEf GdeOQSI GdbOQGhjI GdJi ai OeTb GdMejI JfWb HdSGf MGdgG s
(3BNQgG (B:s
(3hGfUQ Hg GfUGQ GdTQjYI GdfHhjI hjQMe Gddg YHOkG bGd GejfkG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B6s
(3GdfSNI HgG MhGTs
(3JUhas
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdeLGejYs